Tradisi Bapalas Bidan dalam Budaya Lokal antara Ungkapan Syukur dan Tantangan Profesionalime Kebidanan - Ika Mardiatul Ulfa; Aisyah Aisyah; Elvi Elvi; Kiki Andriani; Novia Karolina; Chesi Yolania; Devia Lestari; Eliska Kornelia; Fridolce Bahan; Gea Gea (Pusat riset dan Inovasi Nasional, 2025)
The Bapalas Bidan tradition is a ritual of the Dayak tribe in Kalimantan to express gratitude to the midwife after the birth process. The ritual includes activities such as bathing the baby, serving offerings, and performing a symbolic ceremony to spiritually